COMPARATIVE ANALYSIS OF PROFITS OF AGROTOURISM AND NON-AGRTOURISM ORANGE FARMING BUSINESSES IN PAMATANG SILIMAHUTA DISTRICT SIMALUNGUN REGENCY - Hekdi Theresia Pintubatu; Zuriaini; Irada Sinta (International Conference on Health Science, Green Economics, Educational Review and Technology, 2023)
In Pamatang Silimahuta District, most of the people do orange farming. Facts in the field show that there are two types of citrus farming, namely agrotourism and non-agrotourism citrus farming. Agrotourism citrus farming applies a concept, where visitors can pick directly from the trees at a predetermined price and higher than sold directly to agents. This certainly causes the difference in profits between agrotourism and non-agrotourism citrus farming. This study aims to analyze the amount of profit of agrotourism and non-agrotourism citrus farming and analyze the significant profit difference between agrotourism and non-agrotourism citrus farming in Pamatang Silimahuta District. Sampling in this study used purposive and census methods with a total sample of 46 respondents. The types of data used in this study are primary data and secondary data. Data analysis in this study used a difference test of two free samples (Mann-Whitney test). The results showed that the significance value (0.000) < α (0.05), meaning that there is a significant difference between the average profit of agrotourism and non-agrotourism citrus farming. The results of data analysis show that the average profit of agrotourism farming is greater than non-agrotourism farming.